2017
DOI: 10.5296/ijafr.v7i2.12174
|View full text |Cite
|
Sign up to set email alerts
|

Application of F-Score in Predicting Fraud, Errors: Experimental Research in Vietnam

Abstract: This study investigated the situation of frauds and errors on the financial statements of listed companies on the Ho Chi Minh Stock Exchange. Base on the research model by Dechow, Ge, & Sloan (2011), the authors added a variable is the rate of return on assets (ROA). The research data included 214 enterprises from 2014 to 2016, with 624 observations. The study results showed that three variables including accrual accounting (Rsstacc), accounts receivable customers (Chrec), percentage of asset liquidity (Softas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…Several previous studies on the F-Score model have shown consistent results, which are able to detect fraudulent financial reporting effectively, even better than the Beneish M-Score (Aghghaleh 2016;Hugo, 2019;Hung et al, 2017). In a previous study, Aghghaleh et al (2016) researched companies in Malaysia, Hung et al (2017) researched companies in Vietnam, and Hugo (2019) researched companies in the United States. Previously, Skousen & Twedt (2009) conducted research based on the initial model F-Score in 2007 on emerging market countries and compared to companies in the United States.…”
Section: Introductionmentioning
confidence: 86%
“…Several previous studies on the F-Score model have shown consistent results, which are able to detect fraudulent financial reporting effectively, even better than the Beneish M-Score (Aghghaleh 2016;Hugo, 2019;Hung et al, 2017). In a previous study, Aghghaleh et al (2016) researched companies in Malaysia, Hung et al (2017) researched companies in Vietnam, and Hugo (2019) researched companies in the United States. Previously, Skousen & Twedt (2009) conducted research based on the initial model F-Score in 2007 on emerging market countries and compared to companies in the United States.…”
Section: Introductionmentioning
confidence: 86%
“…The likelihood of fraud is calculated according to the F-score model, which the fraud risk exists when the F-score value is more than 1, and the risk is considered high and very high when the F-score value is more than 1.85 and 2.45 respectively. The model utilized by Hung et al (2017) was also shown to have a fraud predictive capacity of approximately 78%. Aghghaleh et al (2016) empirically investigated the fraud detection and predictive capabilities of the Beneish M-score and the Dechow F-core based on the financial ratios of listed companies in Malaysia from 2001 to 2014.…”
Section: Altman Z-scorementioning
confidence: 99%
“…Conversely, an F-score of less than 1 indicated that there is relatively low risk of financial misstatements. Hung et al (2017) used the F-score model by Dechow et al (2011), to investigate the probability of fraudulent financial reporting in the financial statements of firms listed on the Ho Chi Minh Stock Exchange in Vietnam. They also re-examined the relationship between all the F-score components (RSST accrual (Rsstacc), change in receivables (Chrec), change in inventory (Chinv), soft assets (Softassets), change in cash sales (Chcs), change in ROA (Chroa), actual issuance of stock (Issue), return on assets (ROA), the size of enterprises by revenue (Size) and financial leverage (LV)) and the likelihood of fraud.…”
Section: Altman Z-scorementioning
confidence: 99%
See 1 more Smart Citation
“…/ International Journal of Research in Business andSocial Science, Vol 8 No 4, 2019 ISSN: 2147-4486 Peer-reviewed Academic Journal published by SSBFNET with respect to copyright holders. The F-Score reading result is (Hung, et al (2017)): F-score> 2.45 Very high risk, F-score> 1.85 high risk, F-score> = 1 risk above normal level, and F-score < 1 risk is normal or below.…”
Section: Financial Statement Fraud Riskmentioning
confidence: 99%